Trading people versus trading time: What is the difference? - Goldstein Christine C; Roberts Todd R; Damschroder Laura J; Miklosovic Molly E; Ubel Peter A (BMC, 2005)
Abstract Background Person trade-off (PTO) elicitations yield different values than standard utility measures, such as time trade-off (TTO) elicitations. Some people believe this difference arises because the PTO captures the importance of distributive principles other than maximizing treatment benefits. We conducted a qualitative study to determine whether people mention considerations related to distributive principles other than QALY-maximization more often in PTO elicitations than in TTO elicitations and whether this could account for the empirical differences. Methods 64 members of the general public were randomized to one of three different face-to-face interviews, thinking aloud as they responded to TTO and PTO elicitations. Participants responded to a TTO followed by a PTO elicitation within contexts that compared either: 1) two life-saving treatments; 2) two cure treatments; or 3) a life-saving treatment versus a cure treatment. Results When people were asked to choose between life-saving treatments, non-maximizing principles were more common with the PTO than the TTO task. Only 5% of participants considered non-maximizing principles as they responded to the TTO elicitation compared to 68% of participants who did so when responding to the PTO elicitation. Non-maximizing principles that emerged included importance of equality of life and a desire to avoid discrimination. However, these principles were less common in the other two contexts. Regardless of context, though, participants were significantly more likely to respond from a societal perspective with the PTO compared to the TTO elicitation. Conclusion When lives are at stake, within the context of a PTO elicitation, people are more likely to consider non-maximizing principles, including the importance of equal access to a life-saving treatment, avoiding prejudice or discrimination, and in rare cases giving treatment priority based purely on the position of being worse-off.